The use of smartphones as educational media for optimizing maternal and child health: A qualitative systematic review - Devi Maya Arista; Nurvitriana, Nidya Comdeca; Karunia Wijayanti; Vina Firmanty Mustofa (Universitas Aisyiyah Yogyakarta, 2024)
Introduction: Currently, communication technology shows great potential in exchanging information, including educational interactions for health messages through smartphones. The implementation of this educational communication scope can be a strategy to enhance maternal and child health. Various approaches from different scientific articles necessitate the examination of characteristics, strengths, weaknesses, and outcomes in delivering smartphone-based health education. Purpose: This study aims to review the literature of smartphone uses in implementing maternal and infant care practices. Method: This is a qualitative systematic review was conducted in the databases PubMed, ScienceDirect, and Cochrane using a combination of Medical Subject Headings (MeSH) and relevant keywords: “maternal” OR “mother” OR “pregnant women” AND “child” OR “baby” AND “health education” AND “smartphone” OR “mobile phone” OR “mobile application. Obtained a total of 9 articles for review. Results: This qualitative systematic review discusses 9 articles from several countries and covers 3 main topic themes. These themes included interactive voice response (IVR), direct counseling, and applications (SMS, Social Media, Health Platforms). Conclusion: Based on review, text/SMS messaging on smart phones was better at improving the implementation of maternal and infant care practices